Magnesium Addition Study in Phosphate Recovery from Struvite Mineral Formation - Luluk Edahwati; Sutiyono; A. Khanifah; Lusy Larasati A; Indah N. F. (Future Science, 2023)
An excessive concentration of phosphate in aquatic ecosystems can lead to various problems, such as the proliferation of algae, a phenomenon known as eutrophication. Eutrophication can disrupt the natural flow of water and harm aquatic life. To prevent these issues, it is essential to recover excess phosphate from the water. Phosphate is an essential element for plant growth, playing a vital role in various physiological processes. It accelerates root development, aids in the synthesis of proteins and minerals, promotes flowering and supports overall plant fertilization. The process of phosphate recovery typically involves specific conditions. Moreover, it can serve as a reserve for maintaining phosphate availability in the environment. The extraction of phosphates from water is carried out under specific conditions. This process involves maintaining a temperature of 30°C, with an aeration rate between 0.5 to 1 liter per minute. The pH of the treatment should be maintained within the range of 8 to 10. The molar ratio of Magnesium Ammonium Phosphate (MAP) can vary, with options like 1:1:1, 2:1:1, and 3:1:1. In the context of these parameters, the research findings indicate that the highest phosphate yield was achieved under specific conditions. The optimal conditions for phosphate recovery were a pH level of 8 and a molar ratio of MAP at 2:1:1, resulting in an impressive phosphate yield of 82,19%. These findings emphasize the importance of carefully managing phosphate levels in aquatic ecosystems while also highlighting the potential for efficient phosphate recovery processes to mitigate environmental issues related to excess phosphate concentrations.